KAJIAN PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (L) Merill) var. SINABUNG PADA BERBAGAI JARAK TANAM - Panunggul, Victor Bintang (Universitas Perwira Purbalingga, 2021)
The research of growth and yield soybeans sinabung variety response on crop spacing were aims to determine the crop spacing for growth and soyben production of Sinabung variety.The experimental design used was Completely Randomize Blocks Design (CRBD) with three repetitions.factor different crop spacing consist J1 (20 x 20 ) cm, J2 (25 x 20 ) cm, J3 (25 x 25) cm. The variables measured were fresh plant weight, root wet weight, dry root weight. The results showed that the soybean, crop spacing did not significant effect on growht and yield of soybean Sinabung variety.